1993
DOI: 10.1063/1.464872
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of solvent effects on confined electrolytes

Abstract: Monte Carlo simulations are reported for the solvent primitive model (SPM) of the electrical double layer at electrically charged and neutral surfaces. Both solvent and ions are modeled as hard spheres with interactions governed by hard sphere and Coulomb interactions. Density profiles of solvent and ions and electrostatic potential profiles are presented for 1:1 electrolyte concentrations of 1 and 2 M at 300 K. Comparison of results at charged and neutral walls indicates that the density distribution of a den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 36 publications
(4 reference statements)
4
34
0
Order By: Relevance
“…The electric charge of the electrode repels the cations, while the solvent molecules support their adsorption. The qualitatively similar behaviour of the cations in the vicinity of the electrode was predicted by the DFT [16,20] and MPB [23] theories and also by the earlier MC simulation [22,24]. Consideration of the realistic model of water changes this picture.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The electric charge of the electrode repels the cations, while the solvent molecules support their adsorption. The qualitatively similar behaviour of the cations in the vicinity of the electrode was predicted by the DFT [16,20] and MPB [23] theories and also by the earlier MC simulation [22,24]. Consideration of the realistic model of water changes this picture.…”
Section: Resultssupporting
confidence: 55%
“…The DFT theory has also been applied by other authors [17][18][19][20][21]. The first reliable but scattered Monte Carlo (MC) results were published by Zhang et al [22]. Lamperski et al [23] showed that the modified Poisson-Boltzmann (MPB) extension to solvent molecules was in reasonable agreement with these MC results.…”
Section: Introductionmentioning
confidence: 90%
“…[15] on the basis of a free energy functional detailed below including an approximate Coulomb correlation term [35], for NaCl, KCl and CaCl 2 . For the monovalent ion cases and moderate surface charges σ the correlation term does not significantly modify the predictions based on the mean-field density functional, which yields density profiles in reasonable agreement with Monte Carlo data for a symmetric SPM [15,36].…”
Section: The Semi-primitive Modelsupporting
confidence: 53%
“…For a given ε(z) Poisson's equation ( 36) was solved numerically by a Runge-Kutta method, subject to the boundary conditions: The equilibrium density profiles are determined by minimizing the grand potential per unit area:…”
Section: The Semi-primitive Modelmentioning
confidence: 99%
“…It is usual to take for granted the local charge neutrality between charged surfaces [43][44][45] when dealing with EDL in both theoretical and computational approaches. This is not to be confused with the overall charge neutrality, which clearly has to be always satisfied for a charged system as whole.…”
Section: Introductionmentioning
confidence: 99%